(untitled) (Boletín Semillero de Investigación en Familia, 2023)
Postgraduate training and deepening in different areas of knowledge have become one of the essential elements within higher education institutions, representing the teacher’s qualification and, of course, the contribution and advancement of knowledge. In addition, within a person’s life project they represent an apparent “intellectual status”, misinterpreted nowadays because the title has to “weigh” to understand the moral and social responsibility that it entails. In Colombia, we live in an environment of academic "quality", where the commodification of university degrees with philanthropic discourses are essentially empty and are characterized by praxis that do not promote ideological, social or political debate, but, on the contrary, , are justified on coarse foundations typical of commercial companies. According to the National Accreditation Council (CNA), unlike other Latin American countries, in Colombia, only in the last five years, the number of postgraduate programs has grown more rapidly in master’s degrees and doctorates, in a context where goods and services are offered, sometimes without differentiating characteristics. Clearly, there is today an excessive trend of postgraduate training.